2019
DOI: 10.17509/ijal.v8i3.15252
|View full text |Cite
|
Sign up to set email alerts
|

Task, formulaic language, and role play for developing ESL students’ academic language

Abstract: The effectiveness of task, formulaic language, and role play in facilitating uninhibited communication of ESL learners is beyond doubt. This quantitative empirical research employed a role play communicative assessment and a writing assessment to assess the efficacy of the combination of task, formulaic language, and role play, as a language learning strategy to teach cognitive academic language in English for Specific Purpose classroom of a university. The language ability acquired through brainstorming and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Though certain members presented well and their individual score was good, because of the other members' insufficient contribution to the success of the group, very badly reflected in the accrued group marks. Grouping in a heterogeneous class is not a problem, but group assessment is (29) . When individual members' marks were accrued to make group mark, 2 groups failed because all the team members were either not able or not willing to contribute equally to the team's success.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Though certain members presented well and their individual score was good, because of the other members' insufficient contribution to the success of the group, very badly reflected in the accrued group marks. Grouping in a heterogeneous class is not a problem, but group assessment is (29) . When individual members' marks were accrued to make group mark, 2 groups failed because all the team members were either not able or not willing to contribute equally to the team's success.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Recently, researchers have become interested in the use of formulaic language by learners of English as a second language (ESL; Ebrahimi et al, 2021;Wang & Halenko, 2022). Studies have extensively examined the use of formulaic language in academic English writing (Chen & Baker, 2016;Leelasetakul, 2019;Narkprom & Phoocharoensil, 2022;Staples et al, 2013) and the effects of different teaching methods on developing formulaic language use by ESL learners (Ogawa, 2021;Rajeswaran, 2019). However, Staples and Fernández (2019) found that formulaic language has not been adequately investigated in relation to interlanguage pragmatics, particularly in spoken English discourse.…”
Section: Introductionmentioning
confidence: 99%